Semi-analytic modelling of the europium production by neutron star mergers in the halo of the Milky Way. Issue 4 (12th December 2018) - van Oirschot, Pim; Nelemans, Gijs; Pols, Onno; Starkenburg, Else
ABSTRACT: Neutron star mergers (NSM) are likely to be the main production sites for the rapid (r-) neutron capture process elements. We study the r-process enrichment of the stellar halo of the Milky Way through NSM, by tracing the typical r-process element Eu in the Munich–Groningen semi-analytic galaxy formation model, applied to three high-resolution Aquarius dark matter simulations. In particular, we investigate the effect of the kick velocities that neutron star binaries receive upon their formation, in the building block (BB) galaxies that partly formed the stellar halo by merging with our Galaxy. When this kick is large enough to overcome the escape velocity of the BB, the NSM takes place outside the BB with the consequence that there is no r-process enrichment. We find that a standard distribution of NS kick velocities decreases [Eu/Mg] abundances of halo stars by ∼0.5 dex compared to models where NS do not receive a kick. With low NS kick velocities, our simulations match observed [Eu/Mg] abundances of halo stars reasonably well, for stars with metallicities [Mg/H] ≥ −1.5. Only in Aquarius halo B-2 also the lower metallicity stars have [Eu/Mg] values similar to observations. We conclude that our assumption of instantaneous mixing is most likely inaccurate for modelling the r-process enrichment of the Galactic halo, or an additional production site for r-process elements is necessary to explain the presence of low-metallicity halo stars with high Eu abundances.